PENDEKATAN KOMUNIKASI PADA KOMUNITAS DALAM PENDAMPINGAN ANAK BERKEBUTUHAN KHUSUS - Septo Nurohman; Mutia Rahmi Pratiwi (SOSFILKOM : Jurnal Sosial, Filsafat dan Komunikasi, 2020)
Every child has the right to obtain proper education from formal and non-formal education, including children with special needs. One of the education that is taken through non-formal ways is learning in learning houses or community-based education for children with special needs. Roemah Nanas Semarang is a community that focuses on the advancement of education for children with special needs by developing children's skills and deepening general knowledge to live in the community. This study aims to describe the interpersonal communication approach carried out by teachers in the process of mentoring children with special needs. The method used is descriptive qualitative. The results showed that in the process of mentoring children with special needs, the teachers used a verbal and visual interpersonal communication skills approach. The obstacle faced during the learning process is the diversity of children with special needs in terms of potential and limitations so that a different approach is needed. The result, when a different communication approach is used, the child feels comfortable during the learning process and feels close to the teacher. In further research, it is hoped that it can examine the interaction process in teaching children with special needs and the long-term impact obtained by students in collaboration with the learning process at home and formal schools.